Accelerated degradation tests for reliability estimation of a new product: A case study for washing machines. (April 2014) - De Carlo, Filippo; Borgia, Orlando; Tucci, Mario
Accelerated degradation test is a valuable technique able to provide information on the duration of highly reliable products. It is widely used in electronics, where component life often cannot be estimated in an acceptable time with the classic reliability estimation techniques. In the mechanical engineering sector, however, accelerated degradation tests are not so common. The purpose of this study is to evaluate the applicability of accelerated degradation test methodology to a new mechanical subassembly of a washing machine. In particular, we tried to identify which was the most appropriate degradation parameter, choosing among three possible alternatives. The methodology was applied to the new oscillating group of a washing machine, with oversized dimensions and innovative materials. The first selection of elements that could be monitored initially provided three parameters: the drum deformation, the bearing temperature and the vibrations of the rotation shaft. The research allowed the identification of the deformation as the most appropriate parameter for the reliability estimation of the oscillating unit. The originality of this study lies in the fact that accelerated degradation tests of washing machines is not discussed in earlier studies. In addition, the application of such methodology to select the best from three different parameters is not studied earlier. In this study, another peculiarity of accelerated degradation test has been emphasized: it is possible to quickly enrich the know-how on a new product, allowing an in-depth knowledge of new elements, in far more rapid speed than using the traditional approach.